Treatment of scleroderma-interstitial lung disease with cyclophosphamide is associated with less progressive fibrosis on serial thoracic high-resolution CT scan than placebo: findings from the scleroderma lung study - Goldin, Jonathan; Elashoff, Robert; Kim, Hyun J; Yan, Xaiohong; Lynch, David; Strollo, Diane; Roth, Michael D; Clements, Philip; Furst, Daniel E; Khanna, Dinesh; Vasunilashorn, Srainnapha; Li, Gang; et al. (Chest, 2009)
The Scleroderma Lung Study (SLS) demonstrated significant treatment-associated improvements in pulmonary function and symptoms when patients with scleroderma-related interstitial lung disease (SSc-ILD) were treated with a 1-year course of cyclophosphamide (CYC) in a randomized, double-blinded, placebo-controlled clinical trial. This study examined thoracic high-resolution CT (HRCT) scans obtained during the SLS for treatment-associated changes over time. Ninety-eight of the 158 subjects (CYC group, 49 subjects; placebo group, 49 subjects) participating in the SLS underwent thoracic HRCT scans both at baseline and after 12 months of treatment, which were available for analysis. Two independent radiologists visually scored the baseline HRCT scans for the presence of ground-glass opacities (GGOs), fibrosis (FIB), and honeycomb cysts (HCs) on a scale of 0 to 4. The treatment effect at 12 months was assessed by a blinded comparison of baseline and follow-up scans for evidence of stability and improvement (not worse) or deterioration (worse). At the end of treatment, FIB was significantly worse in the placebo treatment group than in the CYC treatment group (p = 0.014). Furthermore, differences in the 12-month change in FIB between the CYC and placebo groups correlated significantly with other outcome measures, including the 12-month changes in FVC (p < 0.05), total lung capacity (p < 0.05), and dyspnea (p < 0.001) scores. However, no differences were noted between the two groups with respect to changes in either GGOs or HCs. A 1-year course of treatment of SSc-ILD with CYC was associated with treatment-related changes in FIB scores on HRCT scans, which correlated with other measures of treatment response. ClinicalTrials.gov Identifier: NCT00004563.